Competitiveness of the intercity land transport industry in Boyacá, Colombia: an approach to the state of the art - Rodríguez Álvarez, Diego Armando; Pérez Martínez, Rosa Nely (Cooperativismo & Desarrollo, 2016)
Introduction: Competitiveness has become an element that characterizes the dynamics of a sector or organization, and its search has led to the construction and implementation of tools to improve the conditions in which organizations compete in the market. Methodology: Our methodological development was based on the consultation and analysis of documentary sources that allowed the state of research on the sector to be established. This review showed that traditionally there has not been a research interest in the sector, save in its purely technical aspects (on which research has been carried out by institutions of highereducation). The field of its management, however, has not been studied. Results: This research presents the results of a theoretical review of the competitiveness of intercity land transport in Boyacá (Colombia), with the aim of encouraging further research to contribute to the development of this sector in the region.Conclusions: It was concluded that further research is needed on the elements that promote the competitiveness of the sector.
Keywords: quality; competitiveness; transportation trends; intercity land transport